Kerusakan Buah Kakao Akibat Penyakit Busuk Buah (Phytopthora palmivora Butlher) - Wilhelmina Rumahlewang; Handry R.D. Amanupunyo; Bambang S. Tomia (Publikasi Indonesia, 2022)
Phytopthora spp is a pathogen that causes disease in cocoa plants that always attacks cocoa plants and affects the growth of cocoa plants and reduces the quantity and quality of cocoa beans is fruit rot, leaf blight, and stem cancer. This study was conducted to calculate the intensity of cocoa fruit damage due to cocoa fruit rot disease in Waesala Village, Huamual Belakang Sub-district, which is one of the sub-districts in West Seram Regency that cultivates many cocoa plants, namely Waesala, Buano, and Allang Asaude. The method used was survey method with systematic random sampling of 5 sample farmers from 3 villages in Huamual Belakang Subdistrict. The results showed that the average intensity of damage (IK) due to fruit rot disease in Huamual Belakang Subdistrict was 24% (mild category), with an average IK due to cocoa fruit rot in Waesala village of 21% (mild category), Buano 26% (moderate category), and Allang Asaude 29% (moderate category).